A decision support tool for healthcare providers to evaluate readiness and impacts of adopting supply chain data standards (2013)
Healthcare providers are under increasing pressure to reduce waste, eliminate unnecessary costs and redundant efforts, thereby improving the quality and consistency of healthcare delivery. Lack of automation and the lack of use of global identifiers for products and locations, also known as supply chain data standards, are two critical factors that can help streamline providers operations and improve process efficiency. Despite widespread consensus among various stakeholders, healthcare providers lack a well-defined approach towards adopting and implementing data standards. Supply chain data standards can be defined as a set of product and location identifiers which are used in supply chain related processes and transactions.